Why Are We Still Debating Hydroxyethyl Starch Solutions? High Quality and Volume of Evidence of Harm is Conclusive - Konrad Reinhart; Oloan Tampubolon (Majalah Anestesia & Critical Care, 2020)
Fluid resuscitation is indicated to prevent shock and to restore circulatory volume in cases of sepsis and severeblood loss caused by trauma, burns or surgery. Management of Severe Sepsis and Septic Shock” recommend fluid ss first-line therapy for resuscitation of patients with sepsis and septic shock however, synthetic colloids, like HES, are strongly rejected due to safety concerns.Multicentre randomised studies concluded the detrimental effect of HES on organ function, in particular renal function in severe sepsis.Trials demonstrated that HES was associated with increased risk of acute kidney injury (AKI) in patients with sepsis and these findings were later corroborated by further large studies, such as VISEP, CHEST and 6S. These studies have not reported any differences between HES solutions and have concluded that both ‘old’ and ‘new’ HES preparations are associated with an increased risk of kidney injury and mortality.In 2013, following publication of CHEST, VISEP and 6S, which demonstrated increased mortality and AKI/RRT in patients treated with HES, the FDA included details of these adverse events in a black box warning and recommended against the use of HES in critically ill patients. That same year, the EMA pharmaco vigilance risk assessment committee (PRAC) suspended marketing authorisation for all HES products.Given the safety concerns with HES and the current guidance from the FDA and EMA, it is imperative that all physicians are aware of the bans, limitations and risks of using HES. This narrative review aims to discuss the evidence on use of HES in critically ill patients, with a focus on safety data and adverse effects such as acute kidney failure and increased risk of mortality